THE ROLE AND IMPORTANCE OF DIGITAL TECHNOLOGY IN EDUCATION SOX (American Journal of Interdisciplinary Research and Development, 2025)
This article cites the necessary information about the tasks of students in the educational process that should be used in order to develop digital technology. The article describes digital technology, virtual reality, the use of digital technology in education, the advantages of digital technology in educational system Vosti.